Influence of lifestyle, depression, and marital intimacy on quality of life in breast cancer survivors - Su-Jin Seo; Ju-Hee Nho; Myoungha Lee; Youngsam Park (Korean Society of Women Health Nursing, 2020)
Purpose This study investigated lifestyle, depression, marital intimacy, and quality of life (QoL) in breast cancer survivors, with the goal of identifying the impacts of these factors on QoL. Methods A sample of 146 breast cancer survivors was surveyed in this cross-sectional study. Data were collected from March 20 to May 30, 2019, using self-report structured questionnaires at a hospital located in Jeonju, Korea. Data were analyzed using the independent t-test, analysis of variance, Pearson correlation coefficients, and hierarchical regression analysis. Participants agreed to complete a face-to-face interview, including administration of the Health Promoting Lifestyle Profile II, Depression Anxiety Stress Scale 21-Depression Scale, Marital Intimacy Scale, and Functional Assessment Cancer Therapy-Breast Cancer tool. Results QoL was positively correlated with lifestyle (r=.49, p<.001) and marital intimacy (r=.45, p<.001) and negatively correlated with depression (r=-.72, p<.001). Hierarchical multiple regression analysis showed that depression (β=-0.63, p<.001), marital intimacy (β=0.19, p=.001), and lifestyle (β=0.13, p=.031) had significant effects on the QoL of breast cancer survivors, accounting for 63.3% of variance in related QoL. Conclusion This study provides insights into how breast cancer survivors' QoL was influenced by depression, marital intimacy, and lifestyle. To improve the QoL of breast cancer survivors, healthcare providers should consider developing strategies to decrease depression, to increase marital intimacy, and to improve lifestyle.